Efficacy of Rugby Headgear in Attenuating Repetitive Linear Impact Forces - Knouse, Carissa L. (National Athletic Trainers' Association, Inc., 2003)
OBJECTIVE: To determine the effectiveness of rugby headgear and the effect of impact site and headgear type on attenuating repetitive linear impact forces. DESIGN AND SETTING: We obtained 10 headgear of 2 different types (n = 20) from 2 popular manufacturers: type I was Honeycomb headgear and type II was Vanguard headgear. Both headgear types were approved by the International Rugby Board. Headgear were tested according to National Operating Committee on Standards for Athletic Equipment protocols with one modification. The headgear were dropped from a height of 30 cm according to the International Rugby Board standards. Headgear were tested at a National Athletic Equipment Reconditioners Association facility. MEASUREMENTS: We recorded peak acceleration of gravity (g) and Gadd Severity Index readings for each impact. The design of the study was 4 one-way, within-subjects, repeated-measures analyses of variance with alpha = .05. Descriptive statistics were calculated for all categoric variables. RESULTS: Peak g and Gadd Severity Index increased with repetitive impacts, resulting in a headgear's decreased ability to attenuate linear impact forces. Attenuation differed significantly between headgear type I and type II at both impact sites and between the parietal-lateral and occipital impact sites for both headgear types. CONCLUSIONS: The headgear initially attenuated impact forces from a drop height of 30 cm. However, over 10 drops, both headgear decreased in their ability to attenuate repetitive linear impact forces. Decreased attenuation in the occipital region as well as significant differences in attenuation abilities between headgear types support the need for further investigation to examine the efficacy of rugby headgear.